LANGUAGE TEACHERS’ BELIEFS ON MATERIALS USE AND THEIR LOCUS OF CONTROL: CASE-STUDIES FROM IRAN AND JAPAN - Amerian, Majid; Pouromid, Sajjad (Universitas Pendidikan Indonesia, 2018)
Teacher belief research has gone a long way to understand the complex mental lives of language teachers with regards to different aspects of the teaching profession. Little, however, is known about the teachers’ beliefs on the use of language teaching materials. Similarly, attempts to find literature on EFL teachers’ actual use of the materials based on systematic observation meets with great difficulty. The present case study research was therefore designed to contribute to the literature on teacher beliefs and materials use utilizing data from five Iranian and five Japanese teachers of English as a foreign language. Based on questionnaires, observations (50 sessions) and stimulated recall interviews (around 13 hours), it was found that while the Iranian teachers’ beliefs were rooted in their learning and teaching experiences besides the syllabus and context imposed standards, the Japanese teachers’ beliefs were mediated by their learning and teaching experiences, self-developed theories, SLA informed theories and colleague inspirations. The results of stimulated recall sessions making use of the construct of locus of control as interpretive lens also suggested that while the Iranian teachers mostly held other parties responsible for their pedagogic decisions, the Japanese teachers took responsibility for most of their decision on materials use.